1997
DOI: 10.1007/s004320050117
|View full text |Cite
|
Sign up to set email alerts
|

Soluble intercellular adhesion molecule-1 in patients with lung cancer and benign lung diseases

Abstract: Intercellular adhesion molecule-1 (ICAM-1) expression correlates with tumour progression in patients with malignant melanoma or renal cell carcinoma. To assess the value of soluble ICAM-1 (sICAM-1) for lung cancer patients, sICAM-1 was determined by means of an enzyme-linked immunosorbent assay. Sera from 147 patients with lung cancer, from 75 patients with benign lung diseases and from 108 healthy adults were investigated for sICAM-1 expression. Significant differences in sICAM-1 levels were detected in lung … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
6

Year Published

1999
1999
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 23 publications
0
11
0
6
Order By: Relevance
“…In the present study, sICAM‐1 was the only parameter that was significantly elevated in EBC on day −1 in the test group compared with controls. sICAM‐1 in serum is associated with malignant tumours; and although it is a non‐specific marker, it may have prognostic predictive value 25,26 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present study, sICAM‐1 was the only parameter that was significantly elevated in EBC on day −1 in the test group compared with controls. sICAM‐1 in serum is associated with malignant tumours; and although it is a non‐specific marker, it may have prognostic predictive value 25,26 …”
Section: Discussionmentioning
confidence: 99%
“…sICAM-1 in serum is associated with malignant tumours; and although it is a non-specific marker, it may have prognostic predictive value. 25,26 The exclusion of patients with concomitant inflammatory diseases or other potentially stimulating factors from the present study, excluded false increased measurements of mediators. The nonspecific marker CRP was examined as a marker of the inflammatory response.…”
Section: Figurementioning
confidence: 99%
“…Furthermore, the soluble form, sICAM-1, enhances the pro-metastatic phenotype and the pro-inflammatory and pro-tumoral signaling (45). sICAM-1 has been demonstrated to be elevated in the serum of patients with liver metastasis from lung or gastric cancer (46,47), and has been identified as a marker for metastatic stage, disease recurrence and prognosis in non-Hodgkin's lymphoma, hepatocellular carcinoma (HCC), lung cancer, and other cancer types (48)(49)(50).…”
Section: Icam-1 In Liver Metastasismentioning
confidence: 99%
“…11,16 In the study of Sprenger et al, the re was an in cre a se of sI CAM-1 ex pres si on du ring the prog res si on of di se a se co inci ded a po o rer sur vi val prog no sis in the pa ti ents with stab le or fal ling sI CAM-1 le vels. 27 We al so found that sI CAM-1 and VEGF le vels we re hig her in pa ti ents with ad van ced di se a se when compared to pa ti ents with early di se a se.…”
Section: Discussionmentioning
confidence: 70%